Nonlinear generalized cyclic contractions in complete G-metric spaces and applications to integral equations - Nashine, Hemant Kumar Kumar; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2013)
In this paper we introduce generalized cyclic contractions in G-metric spaces and establish some fixed point theorems. The presented theorems extend and unify various known fixed point results. Examples are given in the support of these results. Finally, an application to the study of existence and uniqueness of solutions for a class of nonlinear integral equations is given.